Economic impact and recovery following a global health crisis - Sloboda, Brian W., 1968-; Sissoko, Yaya, 1961- (Advances in finance, accounting, and economics (AFAE) book series., 2022)
"The COVID-19 pandemic has triggered a massive spike in concerns and uncertainties and raised challenges in assessment of the macroeconomic and microeconomic impacts, so this book assesses the economic impacts of the COVID-19 pandemic, covering macroeconomic and microeconomic impacts of COVID-19"--